Resveratrol Reduces Glucolipid Metabolic Dysfunction and Learning and Memory Impairment in a NAFLD Rat Model: Involvement in Regulating the Imbalance of Nesfatin-1 Abundance and Copine 6 Expression - Chen, Xing-Xing; Xu, Ya-Yun; Wu, Rui; Chen, Zheng; Fang, Ke; Han, Yin-Xiu; Yu, Yue; Huang, Ling-Ling; Peng, Lei; Ge, Jin-Fang (Frontiers in Endocrinology, 2019)
Resveratrol (RES) is a polyphenolic compound, and our previous results have demonstrated its neuroprotective effect in a series of animal models. The aim of this study is to investigate its potential effect on a nonalcoholic fatty liver disease (NAFLD) rat model. The parameters of liver function and glucose and lipid metabolism were measured. Behavior performance was observed via the open field test (OFT), the sucrose preference test (SPT), the elevated plus maze (EPM), the forced swimming test (FST), and the Morris water maze (MWM). The protein expression levels of Copine 6, p-catenin, catenin, p-GSK3β, GSK3β, and Cyclin D1 in the hippocampus and prefrontal cortex (PFC) were detected using western blotting. The results showed that RES could reverse nesfatin-1-related impairment of liver function and glucolipid metabolism, as indicated by the decreased plasma concentrations of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBIL), direct bilirubin (DBIL), indirect bilirubin (IBIL), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), glucose, insulin, and nesfatin-1; increase the plasma level of high-density lipoprotein cholesterol (HDL-C); and reduce hepatocyte steatosis in NAFLD rats. Although there was no significant difference among groups with regard to performance in the OFT, EPM, and FST tasks, RES-treated NAFLD rats showed an increased sucrose preference index in the SPT and improved learning and memory ability in the MWM task. Furthermore, the imbalanced protein expression levels of Copine 6, p-catenin, and p-GSK3 in the hippocampus and PFC of NAFLD rats was also restored to normal by treatment with RES. These results suggested that 4 consecutive weeks of RES treatment not only ameliorated glucolipid metabolic impairment and liver dysfunction in the NAFLD rat model, but also mitigated the attendant behavioral and cognitive impairments. In addition to the mediating role of nesfatin-1, the mechanism underlying the therapeutic effect of RES on NAFLD might be associated with its ability to regulate the imbalanced expression level of Copine 6 and the Wnt signal pathway in the hippocampus and PFC.